Add the following algebraic terms 3x, -3x, 5y, 7y.
Hint: Addition in algebraic numbers is similar to the usual numbers. Here we need to add 3x, -3x, 5y, 7y. We’ll add as follows: $ 3x + ( - 3x) + 5y + 7y \\ = 3x - 3x + (5 + 7)y \\ = (3 - 3)x + (12)y \\ = (0)x + 12y \\ = 0 + 12y \\ = 12y \\ $ Hence, 12y is the required solution. Note: Addition, subtraction, multiplication of algebraic expressions is the same as usual numbers but we need to be careful with the divisions because we don’t want 0 in the denominator.